2012
DOI: 10.1530/rep-12-0036
|View full text |Cite
|
Sign up to set email alerts
|

V-ATPase upregulation during early pregnancy: a possible link to establishment of an inflammatory response during preimplantation period of pregnancy

Abstract: Various mechanisms exist to prevent a potentially deleterious maternal immune response that results in compromising survival of semiallogeneic fetus. In pregnancy, there is a necessary early preimplantation inflammatory stage followed by a postimplantation antiinflammatory stage. Thus, there is a biphasic 'immune response' observed during the course of pregnancy. We provide the evidence that capacitation of sperm induced the expression of a2 isoform of V-ATPase (ATP6V0A2 referred to as a2V), leukemia inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
106
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(112 citation statements)
references
References 52 publications
(65 reference statements)
5
106
0
1
Order By: Relevance
“…16 The a2 subunit functions to transport H 1 into the intracellular lumen and also functions as an endosomal pH-sensor. 31 There are several lines of evidence showing that a2V-ATPase is involved in various aspects of mammalian reproduction such as spermatogenesis, 7 sperm capacitation, embryonic development, implantation 32 and placentation. 16 The a2 isoform of VATPase is located specifically in the acrosomal membrane upon capacitation of murine sperm.…”
Section: Seminal Fluid and Immune Response For Embryo Implantationmentioning
confidence: 99%
See 4 more Smart Citations
“…16 The a2 subunit functions to transport H 1 into the intracellular lumen and also functions as an endosomal pH-sensor. 31 There are several lines of evidence showing that a2V-ATPase is involved in various aspects of mammalian reproduction such as spermatogenesis, 7 sperm capacitation, embryonic development, implantation 32 and placentation. 16 The a2 isoform of VATPase is located specifically in the acrosomal membrane upon capacitation of murine sperm.…”
Section: Seminal Fluid and Immune Response For Embryo Implantationmentioning
confidence: 99%
“…Seminal fluid induces pro-inflammatory cytokines and chemokines such as GM-CSF, IL-6, IL-8, MCP-1, MIP-3a, and IL-1a in the female reproductive tract. 32,[35][36][37] Our recent study showed that exposure of sperm to seminal plasma is essential for the infiltration of macrophages in the preimplantation uterus. 32 In addition, capacitation appears to cause the release of a2NTD, which is the N-terminal portion from a2V-ATPase.…”
mentioning
confidence: 99%
See 3 more Smart Citations